2017
DOI: 10.1038/srep44500
|View full text |Cite
|
Sign up to set email alerts
|

ALS Along the Axons – Expression of Coding and Noncoding RNA Differs in Axons of ALS models

Abstract: Amyotrophic lateral sclerosis (ALS) is a multifactorial lethal motor neuron disease with no known treatment. Although the basic mechanism of its degenerative pathogenesis remains poorly understood, a subcellular spatial alteration in RNA metabolism is thought to play a key role. The nature of these RNAs remains elusive, and a comprehensive characterization of the axonal RNAs involved in maintaining neuronal health has yet to be described. Here, using cultured spinal cord (SC) neurons grown using a compartmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 68 publications
4
129
0
Order By: Relevance
“…Notably, little transcriptional overlap existed between the spinal cord and human iPSC-derived motor neurons [90]. Cultured spinal motoneurons expressing mutations in SOD1 G93A and TDP43 A315T showed few alterations in transcriptional expression and an overlap of only 20 transcripts that encoded proteins mainly with predicted extracellular localization [91]. Lumbar spinal motor and oculomotor neurons, which control eye movement and are spared in ALS, showed differences in broad transcriptional profiles of over 1,700 genes some of which presumably indicate a reduced vulnerability of oculomotor neurons to excitotoxicity by enhanced GABAergic transmission [92].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, little transcriptional overlap existed between the spinal cord and human iPSC-derived motor neurons [90]. Cultured spinal motoneurons expressing mutations in SOD1 G93A and TDP43 A315T showed few alterations in transcriptional expression and an overlap of only 20 transcripts that encoded proteins mainly with predicted extracellular localization [91]. Lumbar spinal motor and oculomotor neurons, which control eye movement and are spared in ALS, showed differences in broad transcriptional profiles of over 1,700 genes some of which presumably indicate a reduced vulnerability of oculomotor neurons to excitotoxicity by enhanced GABAergic transmission [92].…”
Section: Discussionmentioning
confidence: 99%
“…While these are excellent tools for separating axons from somas, residual crosscontamination between the compartments still occurs. In this way, RNA-sequencing efforts aimed at isolating an axonal transcriptome profile (Briese et al, 2016;Gumy et al, 2011;Minis et al, 2014;Rotem et al, 2017;Saal et al, 2014;Taylor et al, 2009) can be easily undermined by a failure to carefully examine the purity of axonal fractions. Due to unappreciated technical difficulties, which are not always acknowledged, axonal fractions can be contaminated with other cellular components or non-neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, RNA‐Seq of mutant TDP‐43 (TDP‐43 A315T ) motor neuron axonal samples identified numerous dysregulated mRNAs. Similar to changes seen when SMN protein is lost, TDP‐43 mutation driven alterations in the axonal transcriptome resulted in depletion of mRNAs encoding proteins involved in synapse assembly and axon extension (Rotem et al, ). This similarity in axonal transcriptome changes mirrors the similarity in disease pathology between SMA and ALS.…”
Section: A Highly Complex Populationmentioning
confidence: 96%